Analisis Pelaksanaan Keterwakilan Perempuan di Badan Permusyawaratan Desa (BPD) Klapanunggal - Definitif Mendrofa (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2022)
This study aims to analyze women's participation in the management of the Village Consultative Body. In terms of filling BPD members, one of which is carried out based on women's representation. In this study, researchers will use a qualitative research method with a case study type used as a way to analyze research findings with data collection techniques through literature study and field research in the form of interviews. Research Results Implementation of women's involvement in the Klapanunggal Village Consultative Body has met the requirements for one of the BPD members based on women's representation, namely that of the nine management members of the Klapanunggal BPD there is one woman with a position as a member of the Village Administration and Community Development Sector. However, counseling or outreach to the community needs to be maximized regarding the meaning of gender equality and about women's representation in politics and government.